Inhibition of microRNA‐24 expression in liver prevents hepatic lipid accumulation and hyperlipidemia. Issue 2 (19th May 2014) - Ng, Raymond; Wu, Heng; Xiao, Hong; Chen, Xin; Willenbring, Holger; Steer, Clifford J.; Song, Guisheng
<x xml:space="preserve">Abstract</x> The incidence of nonalcoholic fatty liver disease (NAFLD) and hyperlipidemia, with their associated risks of endstage liver and cardiovascular diseases, is increasing rapidly due to the prevalence of obesity. Although the mechanisms of NAFLD have been studied extensively, the underlying pathogenesis and the role of microRNAs in this process remain relatively unclear. MicroRNA (miRNA)‐dependent posttranscriptional gene silencing is now recognized as a key element of lipid metabolism. Here we report that the expression of microRNA‐24 (miR‐24) is significantly increased in the livers of high‐fat diet‐treated mice and in isolated human hepatocytes incubated with fatty acid. Knockdown of miR‐24 in those mice caused impaired hepatic lipid accumulation and reduced plasma triglycerides. Bioinformatic and in vitro and in vivo studies led us to identify insulin‐induced gene 1 (Insig1), an inhibitor of lipogenesis, as a novel target of miR‐24. Inhibition of endogenous miR‐24 expression by way of miR‐24 inhibitors led to up‐regulation of Insig1, and subsequently decreased hepatic lipid accumulation. It is well established that liver‐specific deletion of Insig1 leads to higher hepatic and plasma triglyceride levels by inhibiting the processing of sterol regulatory element‐binding proteins (SREBPs), transcription factors that activate lipid synthesis. As expected, miR‐24 knockdown prevented SREBP processing, and subsequent expression of lipogenic genes. In contrast, the opposite result was observed with overexpression of miR‐24, which enhanced SREBP processing. Thus, our study defines a potentially critical role for deregulated expression of miR‐24 in the development of fatty liver by way of targeting of Insig1. Conclusion: Our findings show a novel mechanism by which miR‐24 promotes hepatic lipid accumulation and hyperlipidemia by repressing Insig1, and suggest the use of miR‐24 inhibitor as a potential therapeutic agent for NAFLD and/or atherosclerosis. (Hepatology 2014;60:554–564)